2012
DOI: 10.1590/s0100-879x2011007500155
|View full text |Cite
|
Sign up to set email alerts
|

Postural balance in patients with social anxiety disorder

Abstract: Body stability is controlled by the postural system and can be affected by fear and anxiety. Few studies have addressed freezing posture in psychiatric disorders. The purpose of the present study was to assess posturographic behavior in 30 patients with social anxiety disorder (SAD) and 35 without SAD during presentation of blocks of pictures with different valences. Neutral images consisted of objects taken from a catalog of pictures, negative images were mutilation pictures and anxiogenic images were related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“… 13 This decrease in postural sway is probably related to postural freezing phenomenon, 39-41 which is observed in participants who view unpleasant images (mutilated or people in pain). 39-41 It seems that these changes represent a kind of anticipatory anxiety posture, 42 , 43 which in this case was induced threatening situation, in which the platform was elevated platform at different heights.…”
Section: Discussionmentioning
confidence: 93%
“… 13 This decrease in postural sway is probably related to postural freezing phenomenon, 39-41 which is observed in participants who view unpleasant images (mutilated or people in pain). 39-41 It seems that these changes represent a kind of anticipatory anxiety posture, 42 , 43 which in this case was induced threatening situation, in which the platform was elevated platform at different heights.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, demands other than anxiety influence postural control, even in the face of postural threat. For example, Young and colleagues 48 found that study participants with or without compensated vestibular deficits, standing at height or floor level, on a stationary or translating platform used one postural control strategy with eyes open (i.e., stabilization of head in space) and another one with eyes closed (i.e., stabilization of body on the platform). All participants prioritized head stabilization in the eyes-open condition, likely to promote gaze fixation regardless of postural challenges, whereas they favored body stabilization with eyes closed as there was no need to fix gaze.…”
Section: Threat Posture Locomotion and Anxiety In Health And Diseasementioning
confidence: 99%
“…Stabilometry is increasingly widely used, and has been successfully used in patients with social anxiety disorders [ 17 ], in individuals with Parkinson’s disease [ 18 ], and to assess the effects of drugs on postural control, by recording the area that these subjects need to maintain balance [ 19 ].…”
Section: Introductionmentioning
confidence: 99%